2021
DOI: 10.1042/bcj20210212
|View full text |Cite
|
Sign up to set email alerts
|

The cAMP-phosphodiesterase 4 (PDE4) controls β-adrenoceptor- and CFTR-dependent saliva secretion in mice

Abstract: Saliva, while often taken for granted, is indispensable for oral health and overall well-being, as inferred from the significant impairments suffered by patients with salivary gland dysfunction. Here, we show that treatment with several structurally-distinct PAN-PDE4 inhibitors, but not a PDE3 inhibitor, induces saliva secretion in mice, indicating it is a class-effect of PDE4 inhibitors. In anesthetized mice, while neuronal regulations are suppressed, PDE4 inhibition potentiates a β-adrenoceptor-induced saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Conversely, when mice were placed under Isoflurane anesthesia for 10 min before PDE4 inhibitor treatment (see scheme in Figure 3 A), there is no longer a difference in body temperature between solvent- and inhibitor-treated mice, given that anesthesia per se induces significant hypothermia ( Figure 3 B). Importantly, the PDE4 inhibitor Roflumilast produces a similar reduction in serum potassium levels in both awake and anesthetized mice (see scheme in Figure 3 C), suggesting that PDE4 inhibitor-induced hypokalemia occurs independent of, and is mechanistically different from, the various nervous system effects associated with PDE4 inhibition in mice [ 31 , 32 , 33 , 34 , 40 ].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Conversely, when mice were placed under Isoflurane anesthesia for 10 min before PDE4 inhibitor treatment (see scheme in Figure 3 A), there is no longer a difference in body temperature between solvent- and inhibitor-treated mice, given that anesthesia per se induces significant hypothermia ( Figure 3 B). Importantly, the PDE4 inhibitor Roflumilast produces a similar reduction in serum potassium levels in both awake and anesthetized mice (see scheme in Figure 3 C), suggesting that PDE4 inhibitor-induced hypokalemia occurs independent of, and is mechanistically different from, the various nervous system effects associated with PDE4 inhibition in mice [ 31 , 32 , 33 , 34 , 40 ].…”
Section: Resultsmentioning
confidence: 98%
“…Conversely, as a tight regulation of serum potassium levels is particularly critical for the normal function of excitable cells, such as muscle and nerve cells [ 2 , 3 , 5 , 8 , 58 , 79 , 80 ], it is quite feasible that the PDE4 inhibitor-induced reduction of serum potassium levels itself may affect muscle function and neuronal signaling in the animals and may modulate some of their reported physiologic effects such as hypokinesia (skeletal muscle), gastric retention (smooth muscle), or nervous system effects such as hypothermia or salivation [ 31 , 32 , 33 , 34 ]. Indeed, in multiple experiments, PDE4 inhibitor treatment reduces serum potassium levels in individual animals to at or below 3.5 mmol/L, which represents the lower limit of normal serum potassium levels (homeostatic range is 3.5 to 5.3 mmol/L in humans; [ 2 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several methods of saliva collection from preclinical models after cholinergic stimulation have been reported including direct cannulation of excretory salivary ducts (16), vacuum pump suction of saliva from oral cavity (17), glass capillaries (18), micropipette (19)(20)(21), gravimetry using pre-weighed filter paper strips (22) or a swab method (23). However, the methods such as direct cannulation are associated with risk of injury precluding repeated sampling of the gland, while gravimetry, glass capillary and micropipettebased methods show inter-operator variability (23).…”
Section: Introductionmentioning
confidence: 99%
“…A multitude of studies have now shown that the genetic knockdown or deletion of individual PDE4 subtypes in cells and/or animals produce unique phenotypes, indicating that each PDE4 subtype exerts unique and non-overlapping roles in the body [ 2 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Thus, the development of subtype-selective PDE4 inhibitors has been proposed to avert the adverse effects of currently available PAN-PDE4 inhibitors [ 1 , 28 ].…”
Section: Introductionmentioning
confidence: 99%